The immune-related plasma protein LAT2 as a protective modulator in diabetic retinopathy: a Mendelian randomization study - Yang, Ming; Wu, Weizhen (Frontiers in Endocrinology, 2025)
BackgroundDiabetic retinopathy (DR) is a leading cause of vision loss worldwide. Although numerous observational studies have explored candidate biomarkers, the causal contributions of circulating plasma proteins to DR pathogenesis remain largely unclear due to confounding and reverse causality.MethodsTo address this, we performed a two-sample Mendelian randomization (MR) analysis using protein quantitative trait loci (pQTLs) derived from the UK Biobank Pharma Proteomics Project (n = 54,219) and DR outcome data from the FinnGen cohort (n = 96,429; 14,142 cases). Colocalization and transcriptome-based MR analyses were conducted to validate causal protein candidates. We further performed experimental validation in hyperglycemia-induced retinal cells and assessed immune mediation using MR-based mediation analysis. A phenome-wide MR (MR-PheWAS) was also conducted to evaluate disease specificity.ResultsAmong five significant proteins, we identified Linker for Activation of T Cells Family Member 2 (LAT2) as a robust protective factor for DR (OR = 0.358, 95% CI: 0.215–0.597, p < 0.001). Colocalization analysis (PP.H4 = 0.8546) and SMR analysis supported a shared genetic basis between LAT2 expression and DR. LAT2 expression was significantly upregulated under high-glucose stress in retinal cells. Mediation MR revealed that CD27+ switched memory B cells partially mediated the protective effect of LAT2 (mediation proportion: 6.2%, p = 0.047). The MR-PheWAS further confirmed the tissue-specific association of LAT2 with DR.ConclusionsLAT2 may be a potential protective factor for diabetic retinopathy, offering preliminary insight for future biomarker development and prevention strategies.